Changes and Continuity of Islamic Educational Institution Models - A Hasib (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
Informal education is a form of education without a formal curriculum regulated by certain institutions. With this approach, learning is natural and spontaneous, not age-limited, with common goals such as character and value development. The learning process lasts throughout life, and educational materials are adapted to daily needs.Institutions providing informal education, such as families, surrounding communities, and daily environments, play a major role in providing this education. Examples of informal educational institutions include family education, in the surrounding community, character building through daily interaction, religious education in mosques or taklim assemblies, and skills education through practical experience and mentoring. Institutions providing informal education, such as families, surrounding communities, and daily environments, play a major role in providing this education. Examples of informal educational institutions include family education, in the surrounding community, character building through daily interaction, religious education in mosques or taklim assemblies, and skills education through practical experience and mentoring. Institutions providing informal education, such as families, surrounding communities, and daily environments, play a major role in providing this education. Examples of informal educational institutions include family education, in the surrounding community, character building through daily interaction, religious education in mosques or taklim assemblies, and skills education through practical experience and mentoring.